1999
DOI: 10.1348/135532599167860
|View full text |Cite
|
Sign up to set email alerts
|

Measuring influential police interviewing tactics: A factor analytic approach

Abstract: Purpose. This study was concerned with examining the types of tactics employed by police officers to overcome a resistant suspect and elicit a confession to a major crime. The main hypothesis is that tactics that seek to maximize or exaggerate the strength of the evidence against the suspect, or that seek to minimize the suspect's responsibility or role in the offence will be present in serious cases where initial resistance was overcome. Method. The interview data from 18 serious criminal cases were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 5 publications
(9 reference statements)
1
87
0
1
Order By: Relevance
“…Similar fi ndings were reported by Pearse and Gudjonsson (1999), who examined 161 suspect interviews from two London police stations in 1991 and 1992. These researchers found that the most frequent police tactic was to rely on evidence in interviewing.…”
Section: Why Do Suspects Confess?supporting
confidence: 82%
“…Similar fi ndings were reported by Pearse and Gudjonsson (1999), who examined 161 suspect interviews from two London police stations in 1991 and 1992. These researchers found that the most frequent police tactic was to rely on evidence in interviewing.…”
Section: Why Do Suspects Confess?supporting
confidence: 82%
“…Pearse and Gudjonsson (1999;see Gudjonsson, 2003b, for a review) used The Police Interviewing Analysis Framework (PIAF) to analyze social interactions between interviewers and suspects from tape recordings of real-life interrogations and to identify the techniques associated with moving suspects from denial to confession. Each 5-minute segment of interrogation was coded for tactics that were used and suspects' responses, and the results were factor analyzed to identify clusters of events that correlated with one another.…”
Section: Observational Studiesmentioning
confidence: 99%
“…The findings of self-report studies, combined with those derived from naturalistic observations (e.g., Moston et al, 1992;Pearse & Gudjonsson, 1999), suggest that the outcomes of police interrogations result from a combination of factors, which may differ from case to case, rather than individual factors acting in isolation. For this reason, Gudjonsson (2003a) proposed an interactional perspective on interrogation, which can be used to guide research and the clinical assessment of individual cases.…”
Section: Retrospective Self-report Studiesmentioning
confidence: 99%
“…Following the publication of the book, my colleagues and I began to investigate psychological vulnerabilities of persons detained at police stations for interviewing (Gudjonsson et al, 1993), factors associated with confessions and denials (Pearse et al, 1998), the processes and interrogation techniques that made suspects change from an initial denial to a confession in serious criminal cases (Pearse and Gudjonsson, 1999), and the role of personality (Gudjonsson and Sigurdsson, 1999), alcohol withdrawal , and fitness for interview (Gudjonsson et al, 2001).…”
Section: Psychological Vulnerability and Disputed Confessionsmentioning
confidence: 99%